2020
DOI: 10.1186/s12913-020-05272-9
|View full text |Cite
|
Sign up to set email alerts
|

Health care personnel’s perception of guideline implementation for musculoskeletal imaging: a process evaluation

Abstract: Background: The increasing complexity and variability in radiology have significantly fueled the need for guidelines. There are many methods for disseminating and implementing guidelines however; and obtaining lasting changes has been difficult. Implementation outcome is usually measured in a decrease in unwarranted examinations, and qualitative data are rarely used. This study's aim was to evaluate a guideline implementation process and identify factors influencing implementation outcome using qualitative dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…This means that the imaging is still performed; however, the imaging may be more justified than it would have been if it was performed at an earlier stage. 32…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This means that the imaging is still performed; however, the imaging may be more justified than it would have been if it was performed at an earlier stage. 32…”
Section: Discussionmentioning
confidence: 99%
“…However, the feedback missed by the GPs in our study was not referral rated, but rather the quality and justification of their referrals. 32 Reminders have also proven to be effective means to change behavior, 26,36 which potentially could have improved the effect of the implementation. However, it was chosen not to include reminders on the basis of the interviews with GPs and radiologists, as well as discussions with a practice coordinator, where the emphasis was mainly on easy accessibility of guidelines.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are numerous reasons why treatment may or may not adhere to clinical guidelines, such as unfamiliarity with guidelines, disagreement with recommendations, pressure from patients and fear of repercussions (43)(44)(45). Additionally, guidelines are meant only to support decision-making, and not intended as replacement for clinical judgement or to be followed meticulously (46,47).…”
Section: Introductionmentioning
confidence: 99%
“…Previous research [ 6 – 11 ] has identified physicians’ key pain management behaviours (e.g., diagnosing and treating pain, assessing work disability and the need for sick leave, advising patients with pain) and factors that influence these behaviours (physicians’ knowledge and attitudes, external factors). Interventions aiming to promote physicians’ engagement in behaviours recommended by pain management guidelines may affect physicians’ knowledge and attitudes, but changing actual behaviour is more difficult, especially if organizational, workplace and health care system level factors, such as resources, cultures and policies are not targeted [ 12 18 ]. In the OHS intervention, the implementation of the guidelines was supported by three short educational sessions and some coaching sessions for physicians, led by pain specialists.…”
Section: Introductionmentioning
confidence: 99%